Representative volume element size determination for viscoplastic properties in polycrystalline materials. (February 2019) - Yang, S.; Dirrenberger, J.; Monteiro, E.; Ranc, N.
Abstract: The size of representative volume element (RVE) for 3D polycrystalline material is investigated. A statistical RVE size determination method is applied to a Voronoi tessellation-based pure copper microstructure. The definition of RVE has remained problematic in the literature for properties related to nonlinear viscoplastic behavior, e.g. apparent viscoplastic parameter, intrinsic plastic dissipation. Computational homogenization for elastic and plastic properties is performed within a crystal plasticity finite element framework, over many realizations of the stochastic microstructural model, using periodic boundary conditions. The generated data undergoes statistical treatment, from which RVE sizes are obtained. The method used for determining RVE sizes was found to be operational, even for viscoplasticity. The microscale analysis of the full-field simulation results reveals microstructure-relate heterogeneities which shed new light on the problem of RVE size determination for nonlinear properties.